DEMOKRASI DALAM TEOSOFI IBN RUSYD TERHADAP TEORI PLATO - Nur Sakina Harahap; Nur Ikhlas (Jurnal Pemikiran Islam, 2022)
Abstract This study discusses the concept of principles regarding Ibn Rushd's politics he calls his thoughts with the term